(3fUjMI GdVYaGA hEQTGO GdCbhjGAs - (3eMeO GdCejf Hf CMeO RjOGfs; (3Ndjd Hf ESMGb Hf ehSi, VjGA GdOjf GdoLrfpOj GdeGdcj GdeUQj,J (B776 (3g` s ((3ehQjJGfjG s)
(3ChdgG (B:s
(3fGbU hZjQ hGVMI cdeGJg ef BKGQ GdJeRjb hChd GdebQhi ajg gh aCOGg aEfg dGjQLY Hg Ydi GdefUhU aEf CNP MdYkG ef RhLJg djOaYg def VZWg bVi GdNdY ceG dGVZW Ef cGf GdLHQ TQYjkG dbhdg GdBJi heYfi ai LHQ YGed ceG dGVZW ai GdTQGA eef GdLCJg GdMGLI dHjYs
(3BNQgG (B:s
(3fGbU hBNQ GdebQhA ajg ef HGH GdejQGK Khdg hddNfKi GdeTcd fUa fUjHi PcQ hCfKi Ci jCNP fUa eGjQKg ai MGd aQVg PcQ Ch ai MGd aQVg CfKi hdjS GdeYfi Cfg jCNP fUa ejQGK GdPcQ hfUa ejQGK GdCfKi Hd jYfi fUa fUjH GdPcQ hgh Sge hfUa fUjH GdCfKi hgh fUas
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Ydi ghGeTgG TQhM hJUhjHGJs
(3JeRbJ HYV CWQGagG s
(3heYfhfI HGdMHQ GdCMeQ s
(3bQf GdfSN (B:s
Keywords: (3Gdabg GdeGdcjs